Keutamaan Ilmu dalam Perspektif Islam: Transformasi Spiritualitas dan Kontribusi Sosial bagi Kaum Muslim dalam Kitab Mahfudzot Fadhoilul Iman - Mardiyah, Faizah; Rofiq Sofa, Ainur (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2025)
This study aims to examine the virtues of knowledge from an Islamic perspective as taught in the book Mahfudzot Fadhoilul Iman and to explore its relevance in shaping the spiritual transformation of individual Muslims and their social contributions in the modern era. A qualitative approach was employed, utilizing a literature review method to analyze the key principles outlined in the book.The findings reveal that the book Mahfudzot Fadhoilul Iman emphasizes knowledge as the foundation of faith, guiding humanity toward divine truth. Values such as al-ilmu nurun (knowledge is light) and thalabul ilmi faridhatun (seeking knowledge is an obligation) highlight the importance of knowledge as a spiritual means of drawing closer to Allah. Additionally, the principle khairun naasi anfa'uhum linnaas (the best of people are those who are most beneficial to others) underscores the significant social dimension of knowledge in building a prosperous and harmonious society.This study also finds that the values in Fadhoilul Iman remain relevant to contemporary challenges, such as developing education based on Islamic values and applying ethical knowledge in professional fields. By recontextualizing the teachings of this book, Muslims can utilize knowledge as an instrument to strengthen their faith while contributing meaningfully to the well-being of humanity.